Assessing Leadership And Management Abilitities Of Junior Officers From The Perspective Of Soldiers - Hj Saini, Zolkefli (2003)
The intention of this study were firstly to evaluate the perception of soldiers in relation to the leadership and management skills, technical and knowledge skills as well as decision-making skills of junior officers of Signals Corp. It was to sought how junior officers who act as Troop Commanders perform their roles and responsibilities from the perspective of their soldiers they command with the view to gauge their abilities and subsequently providing recommendations from the author if variables under study deemed to have been performed beyond expectation. Secondly, the study was to identify whether the perceptions and opinions of these soldiers can be significantly differentiated between their demographic background such as gender and rank structure. This was essential as a mean to make relevant comparison among those in the ranks in assessing their leaders. In the conduct of this study, data from numerous resources were gathered to include responses from questionnaires and interviews from identified sample size, and other secondary and primary sources. Data collected from samples were coded and analysed by the used of statistical tools and further analysis was supported with in-depth interviews. The literature review from previous studies and theories provided the grounding platform that was extensively used for the formulation of the conclusion. The study concludes that the skills of junior officers under scrutinize were rated relatively moderate from the eyes of their soldiers they command. The soldiers perceived their leaders to possess skills that are just sufficient to perform their role as a leader. The study also concludes that Senior NCOs rated their leaders lower than the rest but no significant differences between gender. According to the author, the level of efficiency potrayed by junior officers was insufficient when the Corp is envisage to meet greater challenges ahead in terms of technological advances in equipment and the dynamic changes in task assignment to the Corp. Thus, the study recommends commitment and dedication from the top by providing appropriate development programs to enhance junior officer’s ability.